2023
DOI: 10.3390/ijms24108481
|View full text |Cite
|
Sign up to set email alerts
|

17β-Estradiol Induced Sex Reversal and Gonadal Transcriptome Analysis in the Oriental River Prawn (Macrobrachium nipponense): Mechanisms, Pathways, and Potential Harm

Abstract: Sex reversal induced by 17β-estradiol (E2) has shown the potential possibility for monoculture technology development. The present study aimed to determine whether dietary supplementation with different concentrations of E2 could induce sex reversal in M. nipponense, and select the sex-related genes by performing the gonadal transcriptome analysis of normal male (M), normal female (FM), sex-reversed male prawns (RM), and unreversed male prawns (NRM). Histology, transcriptome analysis, and qPCR were performed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Histological sections revealed no significant differences between neo-females and dsNRM, when compared to normal dsM and dsFM prawns, with mature sperm in dsNRM and more yolk granules accumulated in dsRM, implying that there was an optimal period for sex reversal. In a previous report, we fed M. nipponense with 17β-estradiol (E 2 ) and found that after a certain period [ 22 ], even high levels of hormones were unable to alter their sex. IAG is responsible for encoding androgens, so we speculate that the sex reversal period in M. nipponense may be influenced by androgen levels in males.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Histological sections revealed no significant differences between neo-females and dsNRM, when compared to normal dsM and dsFM prawns, with mature sperm in dsNRM and more yolk granules accumulated in dsRM, implying that there was an optimal period for sex reversal. In a previous report, we fed M. nipponense with 17β-estradiol (E 2 ) and found that after a certain period [ 22 ], even high levels of hormones were unable to alter their sex. IAG is responsible for encoding androgens, so we speculate that the sex reversal period in M. nipponense may be influenced by androgen levels in males.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Fu et al (2019) conducted research on the CG during different stages of ovarian development and proposed that light signals could impact biological clock gene expression in the nervous system and may reduce steroid hormone secretion [ 33 ]. Notably, we previously used E 2 to reverse sex in male M. nipponense and identified an important sex reversal pathway, “retinol metabolism”, which is also associated with the eyestalks [ 22 ]. In chordates, retinol metabolism plays an important role in the control of cell differentiation, regulation of immune competence, and reproduction during embryogenesis and in the adult organism [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Observations took place using a stereo microscope (SZX16; Olympus Corporation, Tokyo, Japan). Comparative labeling was performed with various cell types based on cell morphology [21].…”
Section: In Situ Hybridization (Ish) and Histological Observationsmentioning
confidence: 99%
“…This suggests that genes controlling growth are likely to be involved in sex differentiation and gonadal maturation. A previous study on the mechanism of sex determination in M. nipponense attempted to identify the "steroid biosynthesis" pathway by comparing the transcriptomes of normal female and unreversed male gonads [21]. A Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis revealed that the genes in this pathway were significantly enriched in sex determination and gonadal differentiation, and LIPA was one of the differentially regulated genes [22].…”
Section: Introductionmentioning
confidence: 99%